2018
DOI: 10.1093/ecco-jcc/jjy143
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated withClostridium difficileInfection in Inflammatory Bowel Disease: A Systematic Review and Meta-Analysis

Abstract: Colonic involvement, biologic and antibiotic use appear to be risk factors associated with CDI amongst IBD patients. CDI is associated with increased short and long-term mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 53 publications
2
38
1
Order By: Relevance
“…Patients who received antibiotics within the first year of life were 2.9 times more likely to develop IBD than those who did (95% CI: 1.2-7.0). Moreover, Balram et al found that antibiotics use within 30 days of diagnosis appeared to increase the risk of clostridium difficile infection (CDI) among IBD patients (OR = 1.85, 95% CI: 1.36-2.52) (138). Therefore, further emphasis should be attached to the management of antibiotics use.…”
Section: Antibioticsmentioning
confidence: 99%
“…Patients who received antibiotics within the first year of life were 2.9 times more likely to develop IBD than those who did (95% CI: 1.2-7.0). Moreover, Balram et al found that antibiotics use within 30 days of diagnosis appeared to increase the risk of clostridium difficile infection (CDI) among IBD patients (OR = 1.85, 95% CI: 1.36-2.52) (138). Therefore, further emphasis should be attached to the management of antibiotics use.…”
Section: Antibioticsmentioning
confidence: 99%
“… 11 Other risk factors include immunosuppression, chemotherapy, acid reduction therapy, prior C. difficile infection, hospitalization, stays in a long-term care facility, and surgeries. 12 , 13 …”
Section: Pathogenesismentioning
confidence: 99%
“…To our knowledge, this study is the first meta-analysis and systematic review to explore the risk factors of CDI in pediatric IBD patients, and assess the impact of CDI on IBD regarding rate of bowel surgery, which is different from that of adults [16].…”
Section: Discussionmentioning
confidence: 99%
“…To date, most studies have demonstrated the risk factors of CDI with IBD in adult patients. In a meta-analysis study, antibiotic use within 30 days, colonic involvement in Crohn's disease (CD) patients, and use of biologics were associated with increased CDI rates [16]. In the pediatric population, conflicting evidence existed when examining potential risk factors for CDI.…”
Section: Introductionmentioning
confidence: 99%